Método de resolução de deadlocks no controle de produção de sistemas de manufatura automatizados utilizando redes de Petri coloridas - Souza, Wesley Willy Oliveira de (2011)
Resources sharing is one of the main characteristics of Automated Manufacturing Systems (SMA), this characteristic can be a synonym of advantages but on the other hand it may lead to the problem of deadlock. Several papers have suggested methods and techniques to reduce or eliminate the occurrence of deadlocks in SMA systems. The deadlock resolution strategies suggested in the literature can be classified into the following types: deadlock detection and recovery, deadlock prevention and deadlock avoidance. This work proposes a resolution method for the control of automated manufacturing systems using colored Petri nets, the main goal of the proposed method is to provide a deadlock-free production controller. To model, simulate and implement the technique in a production controller a dedicated software is used to model the Petri Nets. Initially, a model using Colored Petri Nets is proposed, then changes in the model are introduced in order to eliminate the deadlocks, resulting in a Colored Petri net control model of the SMA. Finally the model is implemented in the scenario of a Flexible Manufacturing System for testing and validation of the method.